Five new species of Coniceromyia Borgmeier (Diptera: Phoridae) from the Atlantic Forest, Brazil - Ament, Danilo Cesar; de Souza Amorim, Dalton (Zootaxa, 2010)
Five new species of Coniceromyia from the Atlantic Forest in Brazil are herein described– Coniceromyia apechoneura, sp. nov., C. brandaoi, sp. nov., C. diaphaniptera, sp. nov., C. franciscana, sp. nov., and C. sanctaetheresae, sp. nov. Both C. diaphaniptera and C. franciscana have patterned wings. The male foretibia provides important diagnostic features for the species, as well as additional characters to propose clades within the genus. The male hypopygial morphology is described.